Antecedent Factors Influencing Manager Competency - Rinto Rain Barry; Hendra Achmadi (Universitas Pelita Harapan, 2024)
Objectives: This study investigates the mediating role of Protestant Work Ethic (PWE) in the relationships between Organizational Culture (OC), Transformational Leadership (TL), and Personality (P) on Teacher Performance (TP) in private Christian elementary schools in Banten Province. Methodology: A quantitative survey was conducted from November 2021 to May 2022, involving 236 Christian elementary school teachers as respondents. Data were collected using questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings: The hypothesis testing results indicate that Organizational Culture positively influences Protestant Work Ethic, while Transformational Leadership negatively affects it. Personality does not significantly impact Protestant Work Ethic. Furthermore, Protestant Work Ethic has a significant positive effect on Teacher Performance. Both Organizational Culture and Personality directly enhance Teacher Performance, whereas Transformational Leadership does not show a significant direct impact. Mediation analysis reveals that Protestant Work Ethic partially mediates the relationship between Organizational Culture and Teacher Performance, as well as between Personality and Teacher Performance, but not between Transformational Leadership and Teacher Performance. Conclusion: The study concludes that OC and P are crucial factors in improving TP, with PWE playing a significant mediating role. TL's negative impact on PWE suggests the need for further investigation into leadership styles within this context. The findings underscore the importance of fostering a positive organizational culture and developing personal competencies to enhance teacher performance.